Rous Sarcoma Virus Translation Revisited: Characterization of an Internal Ribosome Entry Segment in the 5′ Leader of the Genomic RNA - Deffaud, Clarence (American Society for Microbiology, 2000)
The 5′ leader of Rous sarcoma virus (RSV) genomic RNA and of retroviruses in general is long and contains stable secondary structures that are critical in the early and late steps of virus replication such as RNA dimerization and packaging and in the process of reverse transcription. The initiation of RSV Gag translation has been reported to be 5′ cap dependent and controlled by three short open reading frames located in the 380-nucleotide leader upstream of the Gag start codon. Translation of RSV Gag would thus differ from that prevailing in other retroviruses such as murine leukemia virus, reticuloendotheliosis virus type A, and simian immunodeficiency virus, in which an internal ribosome entry segment (IRES) in the 5′ end of the genomic RNA directs efficient Gag expression despite stable 5′ secondary structures. This prompted us to investigate whether RSV Gag translation might be controlled by an IRES-dependent mechanism. The results show that the 5′ leaders of RSV and v-Src RNA exhibit IRES properties, since these viral elements can promote efficient translation of monocistronic RNAs in conditions inhibiting 5′ cap-dependent translation. When inserted between two cistrons in a canonical bicistronic construct, both the RSV and v-Src leaders promote expression of the 3′ cistron. A genetic analysis of the RSV leader allowed the identification of two nonoverlapping 5′ and 3′ leader domains with IRES activity. In addition, the v-Src leader was found to contain unique 3′ sequences promoting an efficient reinitiation of translation. Taken together, these data lead us to propose a new model for RSV translation.